Indirekta anaforer i inlärarsvenska: analys av korta texter skrivna av svenskstuderande i Polen - Kołaczek, Natalia (Folia Scandinavica Posnaniensia, 2019)
Definiteness appears to be one of the most difficult categories for learners of Swedish. Particularly difficult are the so-called indirect anaphors, definite noun phrases without any explicit antecedent in text. The choice of a definite noun phrase in such contexts requires language skills on a higher level and even some general knowledge about the world. Such phrases make a very nuanced category, yet they are marginalised in textbooks for learning Swedish. This paper presents the results of a study conducted among a group of Polish students of Swedish at the Adam Mickiewicz University in Poznań. The analysis considers noun phrases used in contexts for indirect and direct anaphors excerpted from short texts written by the students based on a picture story. The results reveal that the students’ use of indirect anaphors is not stable. It can be assumed that indirect anaphors concerning body parts are easier to acquire for the learners. Another important factor is the relation of possession between anaphors and triggers. Students often omit the suffixed definite article in context for both indirect and direct anaphors. The study is included in my doctoral thesis written on this topic.